Financial Market Integration in Late Medieval Europe: Results from a Threshold Error Correction Model for the Rhinegulden and Basle Pound 1365-1429 - Peter Kugler (Swiss Journal of Economics and Statistics, 2011)
This paper analyzes the integration of the foreign exchange market for the Basle Pound and the Rhinegulden and the market for gold and silver bullion for the period 1365–1429. The application of a threshold error correction model indicates that transaction costs prevent arbitrage when the difference between the gold-silver ratio and the exchange rate is within a 7.4% band, whereas larger deviation exchange rate movements close this gap within one year.
Keywords: N23; 330; Financial market integration; transaction costs; threshold error correction; Basle pound; Rhinegulden